Persepsi pengunjung terhadap kualitas wayfinding sebagai elemen interior di Poliklinik RSIA Limijati, Bandung - Annisa Andrivina (Institut Seni Indonesia Yogyakarta, 2019)
Patient and visitor’s satisfaction is an indicator of the healthcare facility’s quality in hospital. One of the healthcare facilities in hospital is polyclinic area. Indonesia is committed to building a manufacturing industry that is globally competitive through accelerating the implementation of Industry 4.0. In this industrial revolution, there was a big leap where information and communication technology was fully utilized. The health industry also experienced this impact. The digital era in health facilities is a challenge to be better at providing health services to the community. Patient and visitor of health facility are those who are not familiar with the hospital environment and often have poor emotional and physical conditions. Therefore, it required a physical environment that can support the convenience of visitors, especially in the ease of finding the destination. One of the parameters of “design that cares” is to providing convenience for patient and visitor in finding purpose (wayfinding) and oriented in the building. This study is in the form of library research and uses descriptive analysis methods that take samples of patients and visitors of the RSIA Limijati Polyclinic, Bandung. Data were collected by accidental sampling technique through interview, observation, and questionnaire. This research is expected to provide solution to wayfinding design problem related to hospital user’s characteristics, especially polyclinic area. Key words: polyclinic, orientation, wayfinding